2017
DOI: 10.1101/100222
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-annual seasonality of influenza-like illness in a tropical urban setting

Abstract: In temperate countries, influenza and other viral respiratory diseases often have distinct seasonal peaks occurring during colder, wintertime months. However, little is known about the dynamics of influenza and viral respiratory disease dynamics in the tropics, despite high morbidity and a clear epidemiological link between tropical and temperate countries. In temperate countries, the dynamics of influenza and other respiratory diseases are often analyzed using syndromic surveillance data describing influenza-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The ability of current ILI definitions to discriminate between influenza and non‐influenza causes of upper respiratory tract infection in tropical settings has previously been called into question . The clinics in this study also participated in a trial of mobile phone reporting of ILI which demonstrated that ILI symptoms are much more consistent through the year compared to temperate countries and that peaks in ILI activity do not always correlate with peaks in influenza activity . The results of our study demonstrated that although fever, cough and rhinorrhoea were reported more commonly in those who had influenza, such symptoms also occurred in more than 70% of patients with non‐influenza ILI confirming their poor discriminating ability.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The ability of current ILI definitions to discriminate between influenza and non‐influenza causes of upper respiratory tract infection in tropical settings has previously been called into question . The clinics in this study also participated in a trial of mobile phone reporting of ILI which demonstrated that ILI symptoms are much more consistent through the year compared to temperate countries and that peaks in ILI activity do not always correlate with peaks in influenza activity . The results of our study demonstrated that although fever, cough and rhinorrhoea were reported more commonly in those who had influenza, such symptoms also occurred in more than 70% of patients with non‐influenza ILI confirming their poor discriminating ability.…”
Section: Discussionmentioning
confidence: 65%
“…This observational study was conducted between August 2013 and November 2015 at outpatient clinics and community medical practitioners in Ho Chi Minh City (HCMC), Vietnam (private clinics were drawn from the an ongoing mHealth surveillance study ). These clinics were considered representative of primary care within Vietnam .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation